2013
DOI: 10.4300/jgme-d-12-00159.1
|View full text |Cite
|
Sign up to set email alerts
|

The Writing Retreat: A High-Yield Clinical Faculty Development Opportunity in Academic Writing

Abstract: Background The need for consistent academic productivity challenges junior clinician-scholars, who often lack the aptitude to ensure efficient production of manuscripts. Intervention To solve this problem, an academic division of a major medical center developed an off-site writing retreat. The purpose of the retreat was not to teach writing skills, but to offer senior mentor assistance with a focus on the elements of manuscr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 12 publications
0
34
0
Order By: Relevance
“…Although live writer retreats and support groups have been shown to increase productivity in academic publishing,[61516] a live face-to-face course was difficult to achieve in our circumstances, especially in Syria. We found that our low-cost blended online approach (i.e., synchronous sessions via GoToWebinar in addition to posting the recorded sessions on YouTube™ along with posting educational materials and facilitating discussions on Facebook™) was able to reach a large number of early career researchers and students in the Arab region, more than half of them were from Syria.…”
Section: Discussionmentioning
confidence: 99%
“…Although live writer retreats and support groups have been shown to increase productivity in academic publishing,[61516] a live face-to-face course was difficult to achieve in our circumstances, especially in Syria. We found that our low-cost blended online approach (i.e., synchronous sessions via GoToWebinar in addition to posting the recorded sessions on YouTube™ along with posting educational materials and facilitating discussions on Facebook™) was able to reach a large number of early career researchers and students in the Arab region, more than half of them were from Syria.…”
Section: Discussionmentioning
confidence: 99%
“…Such programs have been shown to enhance promotions and educational awards, as well as new educational responsibilities and programs. Programs that provide faculty with direct mentorship in scholarship have been found useful also, as exemplified by an off-site academic writing retreat that has encouraged and succeeded in increasing production of peer-reviewed publications by junior faculty [17].…”
mentioning
confidence: 98%
“…Several different faculty development venues have been demonstrated to increase faculty writing, from day-long retreats to monthly scholarship-focused sessions. 3,14,15 Formal writing workshops can be helpful for junior faculty to help them get started on writing. The American Medical Writers Association developed a toolkit for new writers which may be helpful (http://www.amwa-dvc.org/toolkit/).…”
Section: Go To a Writing Workhop (Or Bring A Workhop Program Or Wmentioning
confidence: 99%